2006
DOI: 10.1002/app.24500
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and crystallization of poly(ethylene terephthalate)/SiO2 nanocomposites by in‐situ polymerization

Abstract: Poly(ethylene terephthalate) (PET)/SiO 2 nanocomposites were prepared by in situ polymerization. The dispersion and crystallization behaviors of PET/SiO 2 nanocomposites were characterized by means of transmission electron microscope (TEM), differential scanning calorimeter (DSC), and polarizing light microscope (PLM). TEM measurements show that SiO 2 nanoparticles were well dispersed in the PET matrix at a size of 10 -20 nm. The results of DSC and PLM, such as melt-crystalline temperature, half-time of crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…The addition of 3.0 wt % Barite and 3.0 wt % SABarite significantly improved the T on by 6.7 and 9.5 °C, respectively. These behaviors are similar to the results reported for the general nanocomposites prepared by in situ polymerization 17. Figure 4(b) shows a decrease (1–3 °C) in melting peak width (Δ T m ).…”
Section: Resultssupporting
confidence: 86%
“…The addition of 3.0 wt % Barite and 3.0 wt % SABarite significantly improved the T on by 6.7 and 9.5 °C, respectively. These behaviors are similar to the results reported for the general nanocomposites prepared by in situ polymerization 17. Figure 4(b) shows a decrease (1–3 °C) in melting peak width (Δ T m ).…”
Section: Resultssupporting
confidence: 86%
“…Yang et al (2006) demonstrated that it is possible to control the crystallization behavior of PET by inorganic nanoparticles. Wang et al (2004) studied the non-isothermal crystallization behavior of pristine PET and PET/clay nanocomposites with a differential scanning calorimeter (DSC), and found that the introduction of clay into PET matrix weakens the dependence of the nonisothermal crystallization exotherm peak temperatures on the cooling rates.…”
Section: From Kementrian Kelautan Dan Perikanan (Ocean and Fisheries mentioning
confidence: 99%
“…Due to high processing temperature of PET, the small organic compounds in the PET melt will be melted, volatilized, or pyrolyzed, and thus the nucleation effect is quite limited. The inorganic compounds are also used as nucleating agents, which need to solve the dispersal problem in the PET matrix [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to high processing temperature of PET, the small organic compounds in the PET melt will be melted, volatilized, or pyrolyzed, and thus the nucleation effect is quite limited. The inorganic compounds are also used as nucleating agents, which need to solve the dispersal problem in the PET matrix [7].According to the crystallization theory, the following requirements are necessary for designing effective nucleating agents. The nucleating agents should have good compatibility with polymer matrix when melt blending [8], high thermal stability and keep solid phase at the crystallization temperature of polymers, as well as large interface for crystal growth [9,10].…”
mentioning
confidence: 99%